Crude protein content in diets associated with intestinal microbiome and metabolome alteration in Huanjiang mini-pigs during different growth stages - Liu, Yating; Azad, Md. Abul Kalam; Zhao, Xichen; Kong, Xiangfeng (Frontiers in Microbiology, 2024)
Introduction: Adequate crude protein (CP) content in diets plays a crucial role in the intestinal health of the animal. This study investigated the impacts of CP content in diets on the intestinal microbiome and metabolome profiles in growing Huanjiang mini-pigs. Methods: A total of 360 pigs with similar body weight (BW) were allocated for three independent feeding trials based on three different BW stages, including (i) 5-10 kg BW, diets consisting of 14%, 16%, 18%, 20%, and 22% CP content; (ii) 10-20 kg BW, diets consisting of 12%, 14%, 16%, 18%, and 20% CP content; and (iii) 20-30 kg BW, diets consisting of 10%, 12%, 14%, 16%, and 18% CP content. These experiments lasted 28, 28, and 26 d, respectively. Results: The results showed that the Shannon and Simpson indices were decreased (P < 0.05) in the ileum of pigs in response to the 14-18% CP compared with the 20% CP content at 510 kg BW stage, while diets containing 12% and 14% CP had higher Chao1 (P < 0.05) and Shannon (P = 0.054) indices compared with 18% CP at 20-30 kg BW stage. Compared with the 20% CP, the diet containing 16% CP displayed an increasing trend (P = 0.089) of Firmicutes abundance but had decreased (P = 0.056) Actinobacteria abundance in the jejunum at 5-10 kg BW stage. In addition, a diet containing 16% CP had higher Lactobacillus abundance in the jejunum and ileum compared with the 18%, 20%, and 22% CP, while had lower Sphingomonas and Pelomonas abundances in the jejunum and Streptococcus abundance in the ileum compared with the diet containing 22% CP (P < 0.05). Diets containing lower CP content altered differential metabolites in the small intestine at the early stage, while higher CP content had less impact. Conclusion: These findings suggest that a diet containing lower CP content (16% CP) may be an appropriate dietary CP content for 5-10 kg Huanjiang mini-pigs, as 16% CP content in diet has shown beneficial impacts on the intestinal microbiome and metabolome profiles at the early growth stage of pigs.